The Bidayuh Ethnic’s Fermented Foods : A Review as Potential Sources of Probiotics. - Iram, Parveen; Samuel, Lihan; Gabriel Tonga, Noweg; Ajibola, Olaide Olawunmi; Kelvin, Egay (2025)
This study reviewsover eight Bidayuh fermented foods (e.g., tipuyak, ,budu,rebung, belacan,tuak, tapai, sawipahit, daun ubi) as probiotic sources. Microbiological analysis shows that plant-based ferments (e.g., tempoyak) are dominated by Lactobacillus, while animal-based ones (e.g., budu) feature halophilic Tetragenococcus. Most Lactic acid bacteria(LAB) isolates exhibit strain-specific probiotic traits: acid/bile tolerance, bacteriocin production, cyanide detoxification, immune modulation, and cholesterol reduction. Safety concerns include high histamine in fish products and cyanogens in rebung will be discussed. Mitigation involves histamine-degrading strains, optimized fermentation, starter quality, and salt control. Although some strains meet FAO/WHO criteria, traditional knowledge loss and insufficient probiotic validation require urgent policy for biocultural protection. More clinical validation and strain documentation are critically needed.